Gender-specific associations between educational status and body weight in the Russian national representative sample - S. A. Shalnova; A. D. Deev; N. S. Karamnova (Кардиоваскулярная терапия и профилактика, 1970)
Aim. In the Russian national representative sample, to investigate gender-specific associations between educational level and body mass parameters: body mass index (BMI), waist circumference (WC), abdominal obesity (AO), as well as the links between education and cardio-metabolic risk (CMR) components – arterial hypertension (AH) and diabetes mellitus (DM).Material and methods. The study included 9686 people aged 24-84 years: 3980 men and 5706 women. Response rate was 87,8%.Results. Higher-educated people demonstrated lower levels of BMI and WC, lower prevalence of AO and clinical states associated with increased BM – AH and AH + AO (р<0,001). Higher-educated individuals also had minimal age-related gradient in BM and WC increase (р<0,001). Educational differences in BM were observed in subjects aged over 25 years (educational status is defined by this age), and were maximal in working-age individuals under 60 years. In older individuals, the association between education and BM was less clear. In men, education was not significantly associated with BM parameters, while in women, this association was statistically significant (р<0,001). In lower-educated women, odds ratios (ORs) for AO, AH, and their combination were, respectively, 2,4 (95% CI 2,0-2.9), 1,6 (95% CI 1,4-1,95), and 1,95 (95% CI 1,6-2,4). In women with secondary education, respective ORs were 1,95 (95% CI 1,7-2,3), 1,2 (95% CI 1,0-1,4), and 1,5 (95% CI 1,2-1,8), comparing to their peers with higher education. Among men, OR for AH was 1,6 (95% CI 1,3-1,9) in the lower-educated and 1,3 (95% CI 1,1-1,6) in those with secondary education.Conclusion. Among women, educational level was significantly linked to BM parameters and BM-related characteristics of AH and AO. In men, this association was observed for AH only.